Regulation of digital trade in US Free Trade Agreements: From trade regulation to digital regulation - GAO, Henry S. (Institutional Knowledge at Singapore Management University, 2018)
This article reviews the evolution of rules on digital trade in US Free Trade Agreements (US FTAs), and argues that the US approach has shifted from treating it largely as a traditional trade issue to recognizing its unique digital nature and tailoring the rules accordingly, as it has done in the Trans-Pacific Partnership (TPP) Agreement. The article begins with a review of the efforts to regulate e-commerce in the WTO, as well as the achievements of the pre-TPP US FTAs so far, followed by a critical appraisal of the strengths and weaknesses of the e-commerce chapter in the TPP. It is hoped that, by reviewing the evolution of the regulation of e-commerce from theWTOto the TPP, we can learn some lessons on how the rules are being shaped, as well as how they might evolve in the future.